2019
DOI: 10.1177/2399808318821112
|View full text |Cite
|
Sign up to set email alerts
|

Noise and the city: Leveraging crowdsourced big data to examine the spatio-temporal relationship between urban development and noise annoyance

Abstract: Noise is one of the most frequently complained nuisances and public health hazards. While traffic-related noise has been studied extensively, research on construction noise has been lacking. In this study, we examined the relationship between construction activities and noise annoyance and tested whether this relationship is stronger during after-hours. Data were drawn from a historical inventory of major development projects and crowdsourced citizen complaints data (311 calls) in Vancouver, Canada from 2011 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 67 publications
(89 reference statements)
1
21
0
Order By: Relevance
“…Despite these challenges, big data "can reveal new dynamics, can allow for the study of certain processes in real time and can highlight relationships and correlations that may pass unnoticed using classical methods and data" (Shearmur 2015). Big data can lead to insights at spatial and temporal scales not previously possible (Zhou et al 2019;Hong et al 2019). Through new insights on the use of big data in transportation and smart cities, this study supports both the research and practice of transportation planning.…”
Section: Introductionmentioning
confidence: 53%
“…Despite these challenges, big data "can reveal new dynamics, can allow for the study of certain processes in real time and can highlight relationships and correlations that may pass unnoticed using classical methods and data" (Shearmur 2015). Big data can lead to insights at spatial and temporal scales not previously possible (Zhou et al 2019;Hong et al 2019). Through new insights on the use of big data in transportation and smart cities, this study supports both the research and practice of transportation planning.…”
Section: Introductionmentioning
confidence: 53%
“…Hong et al [42] studied crowdsourced big data based on noise complaints from the 311 system, which is the full-time non-emergency telephone services and online platform, in Vancouver, British Columbia, Canada. The utilized 311 data were classified as either “noise complaint case” or “general noise inquiry case” from 2011 to 2016, and were compared with the location and geographic information of noise.…”
Section: Discussionmentioning
confidence: 99%
“…Making a noise complaint is a behaviour related to noise level and perception. A general assumption is that not everyone who experiences noise issues complains; however, noise complaints can give useful indications regarding those areas in which people are bothered by noise (Hong et al, 2019;Public Health England, 2018).…”
Section: Noise Complaints Datasetmentioning
confidence: 99%
“…Zheng et al (2014) developed a model to recover the noise situation throughout NYC where they used noise complaint data. Hong et al (2019) found, using longitudinal administrative data from 2011 to 2016, that an increase in construction activity of one-unit in a cell based on heat maps was associated with an approximately 6% higher incidence rate of noise complaints. However, the research on how urban planning affects noise complaints is currently inadequate.…”
Section: Introductionmentioning
confidence: 98%